(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As the main goal of the efficiency program, any maintenance department management has to analyze its activities to strive for an excellent performance. One area of improvement is to maintain maintenance work order management. The point of the activity is to reduce the work order backlog. Managing a significant number of backlogged work orders and the resources required to reduce the work order backlog is critical to having a high-performance maintenance organization. This research is focused on finding the root causes of increasing the work-order backlog in a petrochemical company, leading to the low maintenance performance in the company. A fishbone diagram is used to analyze the root cause of delayed maintenance activity and each aspect of cause rendered into the questionnaire to capture the occurrence, severity, and detection to gain a total score. The finding shown that backlogs do not interfere with the production process so that the product can meet the needs of consumers are 10% of the total work orders that are released each year. The analysis obtained shows that backlog work orders that occur at Petrochemical Company account for 16% of the total Work Orders that are released in March 2019. Preventive and predictive maintenance was applied to improve the equipment reliability in Petrochemical Company and reduce up to 6 % of the backlog in April 2020. the preparation of a maintenance information system with a Computerized Maintenance Management System (CMMS) so that information about machine failure data can be used as a reference to analyze machine conditions and become a reference for making policies.